Perinatal and obstetric-neonatal outcomes following frozen embryo transfer cycles with a thinner endometrium: a retrospective study - Xin Li; Ting Luan; Jueyun Lu; Yi Wei; Juanjuan Zhang; Chun Zhao; Xiufeng Ling (BMC Pregnancy and Childbirth)
Abstract Objective The purpose of this study was to evaluate the relationship of thin endometrial thickness (EMT) on the maternal and child health outcome of frozen-thawed embryo transfer (FET) cycles with singletons. Methods The retrospective cohort study included 1,771 live singleton deliveries, with 273 in the thin endometrium group (EMT ≤ 7.5 mm) and 1,498 in the control group (EMT > 7.5 mm). Pregnancy, perinatal complications and neonatal outcomes were compared between the two groups. Results Women in the thinner endometrium group had higher rates of preeclampsia (7.69% vs. 7.00%), placenta previa (4.39% vs. 2.43%), postpartum haemorrhage (15.38% vs. 11.42%) than the control groups, although they were not significantly different. Significant difference was observed in the rates of placental abruption (1.09% vs. 0.07%, P = 0.001), abnormal placental cord insertion (3.66% vs. 1.74%, P = 0.011), placental adherence (15.38% vs. 7.14%, P < 0.001) between the two groups. No significant difference could be found regarding preterm labour, macrosomia, Apgar ≤ 7, large for gestational age (LGA) and appropriate for gestational age (AGA), and singletons from the thinner endometrium group had a significantly lower birthweight than those from the controls. Then after adjusting for confounders, thinner endometrium was still statistically significantly associated with placental adherence, postpartum haemorrhage and low birthweight (LBW). Conclusion These findings highlight the important role of endometrial thickness in influencing perinatal and obstetric-neonatal outcomes in FET cycles. The study contributes to the growing body of evidence supporting the clinical relevance of endometrial thickness in FET cycles and underscores the need for close monitoring and management of pregnancies in women with a thin endometrium. Future research should focus on elucidating the underlying mechanisms and identifying effective interventions to improve endometrial thickness and pregnancy outcomes in this patient population.